Dampak Reward dan Punishment terhadap Kinerja Karyawan Melalui Disiplin Kerja Sebagai Variabel Intervening di PERUMDA Air Minum Tirta Batang Hari - Sufriyan Wahyudin Darmanto; Sry Rosita; Dian Mala Fithriani Aira (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to determine the impact of rewards and punishments on employee performance through work discipline. This study uses quantitative methods, data collection techniques by distributing respondent questionnaires. The sample in this study were 48 employees of PERUMDA Air Minum Tirta Batang Hari. This study uses Descriptive Analysis techniques using the SmartPLS 4.0.0 application as a data processing tool. The results of this study indicate that rewards have a positive and significant effect on performance. Punishment does not have a positive and significant effect on performance. Work discipline has a positive and significant effect on performance. Rewards have a positive and significant effect on work discipline. Punishment has a positive and significant effect on work discipline. Rewards have a positive and significant effect on performance through work discipline. Punishment does not have a positive and significant effect on performance through work discipline.